Dietary chlorogenic acid regulates gut microbiota, serum-free amino acids and colonic serotonin levels in growing pigs. (4th July 2018) - Wu, Yi; Liu, Wenhui; Li, Qi; Li, Yafei; Yan, Yali; Huang, Fang; Wu, Xin; Zhou, Quancheng; Shu, Xugang; Ruan, Zheng
Abstract: Chlorogenic acid (CGA) has many biological properties, including antibacterial, antioxidant and anti‐inflammatory properties, and is one of the most abundant phenolic acids available in the human diet. The aim of this study was to investigate the effects of CGA on regulation of the gut microbiota, and on the levels of free amino acids and 5-hydroxytryptamine (5-HT, serotonin). Ninety-six healthy growing pigs were randomly assigned to two treatment groups: the Ctrl group (control group, standard feed) and the CGA group [standard feed plus 0.05% 3-caffeoylquinic acid (3-CQA)] for 60 days. The diversity of the gut microbiota was increased after CGA supplementation. Changes in these microbes were significantly associated with the serum free amino acid levels and colonic 5-HT level. Compared with the Ctrl group, the levels of serum aspartic acid, threonine, alanine, arginine, and colonic 5-HT were significantly increased ( p  < .05). These data suggest important roles for CGA in regulating the gut microbiota and increasing the serum free amino acid levels.